2019
DOI: 10.4274/uob.galenos.2018.1113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Testicular Self-examination Technique and Testis Cancer Knowledge Levels of Final-year Medical Students

Abstract: The aim of this study was to evaluate the adequacy of knowledge regarding testicular self-examination (TSE) in final-year medical students and determine the TSE performance rate among male students. Materials and Methods: This cross-sectional study was conducted with final-year students in the Meram Medical Faculty of Necmettin Erbakan University in the 2015-2016 academic year. The target population of the study was 233 people and all 202 people who agreed to participate in the survey were included. A data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…In the study, it was determined that over half of all students had not received any information about TSE. Similar to our findings, Uyar and colleagues stated that only about 26% of final‐year medical students knew how to perform TSE 32 . Moreover, in a related study conducted with undergraduate nursing students, it was reported that previously percentage of informed related to testis cancer was 17.1% 33 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the study, it was determined that over half of all students had not received any information about TSE. Similar to our findings, Uyar and colleagues stated that only about 26% of final‐year medical students knew how to perform TSE 32 . Moreover, in a related study conducted with undergraduate nursing students, it was reported that previously percentage of informed related to testis cancer was 17.1% 33 .…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, among studies conducted with students in health sciences in our country, there are studies in which rates of performing TSE regularly are lower 11.1%, 37 17.7%, 22 21.5% 38 and 32.1%. 32 In our study, 59.6% of students stating that they performed TSE were nursing faculty students. It was seen that the percentage of nursing faculty students who had knowledge/had received information about TSE (59.6%) and who performed TSE (59.6%) was higher and constituted a significant difference compared to students of the other faculties (Table 2).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Although testicular cancer ranks first among the most common types of cancer in men aged 15-24 in Turkey, the limited number of intervention studies and trainings on testicular cancer in the literature has revealed the need for studies in this area. Based on the information in the literature and the inadequacy of early diagnosis activities, it is seen that there is a lack of information about TSE and it would be beneficial to include different education models in adult education.…”
Section: What This Paper Addsmentioning
confidence: 99%